Research on The Relationship Between Pay Gap and Job Performance - Niu, Yutao (Transactions on Economics, Business and Management Research, 2024)
With the advent of the information age, the efficiency and convenience of information sharing and acquisition make employees’ perception of pay gap more and more clear, which will affect employees’ attitudes, behaviors and job performance. There are three representative views on the influence of pay gap on job performance, namely tournament theory, behavior theory and contingency theory. This paper reviews the related literature about the influence of pay gap on job performance at home and abroad, sorts out the different factors that affect the relationship between them in order to provide reference for formulating job pay policy.